Recovery of gold in sulfide minerals of low grade in the region of Casma - Aramburú Rojas, Vidal (2017)
The representative sample of low grade sulphide ore gold for this research study comes from the province of Casma Ancash department.The characterization of the sample was analyzed in the polarized light microscope, in the EAP. Geological Engineering at the National University of San Marcos (UNMSM), the results indicated the presence of the following mineralogical species such as Electrum, sphalerite, ilmenite, pyrite, hematite, goethite and bargains. Furthermore we found particles referred to gold, which are: Electrum-goethite, Electrum-Gangas, Electrum-goethite- Gangas.Based on the results of the characterization we realized metallurgical process like preconcentration Falcon performed in the concentrator, the results of the most representative process is 67.80%, obtaining in a granulometry of -200mesh, obtaining a concentrate grade of 16.20 g / TM, 57.04% of 41.60 radio recovery and concentration.With the tailing of the most representative test preconcentration, several metallurgical flotation tests were conducted, the most representative test was obtained, using 74.10 g / TM collector (AR1208), obtaining a concentrate grade of 11.36 g / TM, 92.27 and 88.11% recovery of concentration radio.Preconcentration and flotation,the concentrate of those process were joined and passed by remolienda, obtaining the Last granulometry of 80.27% -200 mesh with a head grade of 15.78 g / TM and with those results were realized metallurgical cyanidation process in bottled, but in different times, the most representative test is 72 hrs. cyanidation, yielding 87.94% gold recovery and a sodium cyanide consumption of 1.65 kg / TM.